Interpersonal Psychotherapy as a Single Treatment for Borderline Personality Disorder: A Pilot Randomized-Controlled Study - Bozzatello, Paola; Bellino, Silvio (Frontiers in Psychiatry, 2020)
Recent guidelines share the recommendations that psychotherapy plays a central role in the treatment of borderline personality disorder (BPD). In recent years, interpersonal psychotherapy adapted for treating BPD (IPT-BPD) was added to specific psychotherapies and was tested in combination with pharmacotherapy. The present study is aimed to assess the efficacy of IPT-BPD revised (IPT-BPD-R) as single treatment in a sample of BPD patients. Results obtained in a group of patients receiving IPT-BPD-R were compared with those observed in a control group in waiting list plus clinical management (WL/CM). Forty-three BPD subjects were randomly allocated to one of the two arms. Patients were assessed at baseline and after 10 months with the following assessment instruments: Clinical Global Impression Scale, Severity item (CGI-S), Social Occupational Functioning Assessment Scale (SOFAS), Borderline Personality Disorder Severity Index (BPDSI), Barratt Impulsiveness Scale, version 11 (BIS-11), Modified Overt Aggression Scale (MOAS), and Self Harm Inventory (SHI). Statistical analysis was performed with one-way analysis of variance (ANOVA) or chi-square test to compare baseline characteristics of the two treatment groups. Comparison of score changes at the end of the trial between the two groups was calculated for each rating scale with the analysis of variance for repeated measures. Seven patients (16.3%) discontinued the treatment in the first month of the trial for non-adherence. We found a significant effect within subjects (trial duration) for all rating scales, except for the MOAS. A significant effect between subjects (treatment modality) was found for CGI-S; SOFAS; BIS-11 total score and subscale “non-planning impulsivity”; BPDSI total score and items “interpersonal relationships”, “impulsivity”, and “identity”. So, results showed differences between groups in favor of psychotherapy in terms of reduction of severity of general psychopathology, improvement of social and occupational functioning, and decrease of global BPD symptoms and three specific domains. On the other hand, we did not find any differences between groups for self-harm behaviors and aggressive behaviors.